Влияние заместительной сурфактантной терапии на показатели оксигенации при термоингаляционном поражении - Пылаев, А.В.; Бабанин, А.А.; Пылаева, Н.Ю. (Таврический медико-биологический вестник, 2012)
Досліджено парціальний тиск кисню, індекс оксигенації та альвеолярно-артеріальну різницю по
кисню D(А-а)O2
у пацієнтів з термоінгаляційним ураженням (ТІУ) на тлі застосування препарату
екзогенного сурфактанта «Сузакрін» в доповнення традиційного комплексу лікування ТІУ. Отримані
дані свідчать про підвищення показників оксигенації, що дозволяє рекомендувати «Сузакрін» для корекції
дихальних порушень у постраждалих з ТІУ. The partial arterial oxygen tension, oxygenation index, and alveolar-arterial difference in oxygen
concentration in patients with thermoinhalation injuries (TII) have been studied with the exogenous surfactant
preparation «Susacrine» used as an addition to the traditional complex treatment of TII. The data obtained
show improvement of the oxygenation parameters, thus “Suzakrin” can be recommended for treatment of
respiratory disorders in patients with TII.